Menschen mit Behinderung in einer gerechten Gesellschaft: Eine theologisch-ethische Perspektive - Schockenhoff, Eberhard (ET studies, 2013)
In the first part, the article deals with the necessary distinction between the medical, cultural and social aspects of physical and mental handicap, and the consequent shift from an understanding of physical and mental handicap oriented towards disability to one that focuses on positive abilities. The Annex to the international document of the World Health Organization and the UN Convention on Handicaps of 2008 emphasized that the law on the social inclusion of handicapped people should be approached within a universal understanding of human development and human rights. The second part asks why the human rights of handicapped people are not adequately considered in influential statements in philosophical ethics (classical Utilitarianism, Preference Utilitarianism, contractual theories and ideas of autonomy) and adequately grounded in the face of the demand for a juridical ethic of universal benevolence that is close to the Christian commandment to love one’s neighbour and to a form of care that is not patronising. The third part discusses the standing and limits of theological attempts to answer the question about the meaning of physical evil such as illness, grief and handicaps. This reflection exposes the presuppositions under which bodily phenomena and mental impairments can be assigned in this threefold group, understood as elements of a contingent creation, while rejecting the classical theological interpretation of original sin.